Social Work Practice and Rural Development. A Case Study of Kyanamira Sub-County Kabale District. - Ssembure, Edson (Kabale University, 2024)
The study focused on the findings of the challenges of social work and social administration in the rural development of the Kabale district. The objectives of the study included the following to identify the contribution of social work and social administration on rural development, to find out the challenges faced by social work and social administration on rural development, and to identify the strategies in place to increase the role of social workers towards rural development. There was a critical review of the issues that have been explored and studied both theoretically and empirically in the existing literature on of social work and social administration as an independent variable and rural development as the dependent variable and the methods of data collection were put into action. The research used 45 respondents as the sample size, and both qualitative and quantitative methods of data collection and analysis were employed. The researcher used simple random sampling techniques in collecting and analyzing data and was used to provide equal chances to the sample size. Purposive sampling was also used to collect data from respondents who participated in the study. Findings of the study were obtained from the field interpreting the results analyzing based on the specific objectives of the study chapter five portrayed the summary of findings, recommendations were made such as to curb some of the challenges experienced by social work and social administration, Social work education and profession have greater responsibility in the process of community development. Hand-by-hand support of education and field practice can contribute to the welfare of the various sections of society. Therefore there is a need of well qualified, practiced, and committed social workers, they can work to improve the socio-economic status, and quality of life for community members the study concluded that social work and social administration is a vibrant profession; longitude and latitude of the profession are largely widened. The direct roles of social workers begin with practicing primary methods of social work. Primary methods are the participatory methods with the individual, group, and community. Secondary methods are both participatory and non-participatory to be used for the benefit of society at large. Therefore the role of social workers and social administration is widened for the betterment of individuals, groups, and communities. Social workers may play all of these roles and contribute in different contexts and at different times in their careers; the contributions have been documented in this report.